Effect of statin use on pain relief by transforaminal epidural steroid injection. (April 2016) - Sari, Sinem; Aydın, Osman Nuri; Tasdemir, Banu; Galimberti, Fabrizio; Turan, Alparslan
Aim: To investigate the impact of statin use on response to fluoroscopy-assisted transforaminal anterior epidural steroid injection (TAESI). Methods: Patients undergoing TAESI for low back pain were recruited and stratified according to statin use. Pain was evaluated with a visual analogue scale (VAS) before and at 1, 3, and 6 months after TAESI. Health-related quality-of-life was evaluated using the Short Form 36 (SF-36) questionnaire 6 months after TAESI. Results: There were no significant differences in VAS scores after TAESI between statin users ( n = 40) and statin nonusers ( n = 253). The SF-36 subgroup: role limitations due to emotional problems score was significantly lower in statin users than statin nonusers. There were no significant between-group differences in any other SF-36 parameter. Conclusion: Statin use had no effect on pain scores after TAESI.